Pengaruh Model Problem Based Learning terhadap Hasil Belajar Peserta Didik Tema Makanan Sehat Subtema Tubuh Mengolah Makanan Pb 1 Kelas V SD Negeri 1 Indrajaya Kabupaten Aceh Jaya - khairati, khairati; Nurhaidah, Nurhaidah; Safiah, Intan (Elementary Education Research, 2023)
Problem Based Learning is a teaching model with a focus on real problem solving, a process where students carry out group work, feedback, discussions that can serve as a stepping stone as an investment and investigation and final report so that students are encouraged to be more actively involved in learning materials. and develop critical thinking skills. The formulation of the problem in this research is whether there is an effect of the Problem Based Learning Model on the learning outcomes of students with the theme Healthy Food, Body Processing Food, Pb 1 Class V at SD Negeri 1 Indrajaya, Aceh Jaya Regency. This study aims to determine the significant effect of the Problem Based Learning Model on the learning outcomes of students with the theme Healthy Food, Body Processing Food, Pb 1 Class V at SD Negeri 1 Indrajaya, Aceh Jaya Regency. The hypothesis in this study is that there is a significant effect of the Problem Based Learning Model on student learning outcomes with the theme Healthy Food, Body Processing Food, Pb 1 Class V at SD Negeri 1 Indrajaya, Aceh Jaya Regency.This research approach is a quantitative approach, a quasi-experimental type of research with One Group Pretest Posttest Design. This research was conducted at SD Negeri 1 Indrajaya, Aceh Jaya Regency. Sampling was done using saturated sampling technique and the samples in this study were all fifth grade students at SD Negeri 1 Indrajaya, Aceh Jaya Regency. Data collection techniques using tests, namely pretest and posttest. And the data analysis technique used t-test at a significant level = 0.05. From the data analysis, it was obtained that thitunng ttable = 24.63 1.714. Based on the criteria for testing the hypothesis, it was found that Ho was rejected and H1 was accepted. So the conclusion in this study is that there is a significant effect of the Problem Based Learning Model on student learning outcomes with the theme of Healthy Food, Body Processing Food Sub-theme Pb 1 Class V at SD Negeri 1 Indrajaya, Aceh Jaya Regency is accepted.